Development of a Numerical Characterization Method for a Ducted Savonius Turbine with Power Augmenters - Sebastian Brusca; Filippo Cucinotta; Antonio Galvagno; Felice Sfravara; Massimiliano Chillemi (Energies)
Savonius turbines are widely used in energy recovery applications, including urban-integrated wind energy systems and Oscillating Water Column (OWC) setups for wave energy conversion. This study explores the use of a ducted Savonius turbine. Experimental tests were conducted on a scaled turbine to evaluate its performance. A Computational Fluid Dynamics (CFDs) model, incorporating Sliding Mesh and Dynamic Fluid Body Interaction (DFBI) techniques, was developed to replicate the experimental conditions. The accuracy of the model was confirmed through validation against experimental data. In total, four conditions were studied: one without a Power Augmenter, one with the Bell-Metha Power Augmenter, and two custom ones obtained by increasing the slope at the end of the Power Augmenters. To facilitate rapid turbine characterization, a fast computational method was developed, allowing the derivation of characteristic curves using only three CFD simulations per configuration. The reliability of this approach was assessed by comparing predictions with experimental results. Developing such a model is crucial, as it enables seamless integration with Reduced-Order Models (ROMs), significantly improving efficiency in evaluating multiple operating points. Compared to traditional experimental testing, this approach provides a faster and more efficient way to obtain performance insights, paving the way for enhanced turbine optimization and real-world deployment.